Constructing a Novel Dendron for a Self‐Host Blue Emitter with Thermally Activated Delayed Fluorescence: Solution‐Processed Nondoped Organic Light‐Emitting Diodes with Bipolar Charge Transfer and Stable Color Purity. Issue 2 (20th December 2016) - Ban, Xinxin; Lin, Baoping; Jiang, Wei; Sun, Yueming
Abstract: Self‐host thermally activated delayed fluorescence (TADF) materials have recently been identified as effective emitters for solution‐processed nondoped organic light‐emitting diodes (OLEDs). However, except for the carbazole unit, few novel dendrons have been developed to build self‐host TADF emitters. This study reports two self‐host blue materials, tbCz‐SO and poCz‐SO, with the same TADF emissive core and different dendrons. The influence of the peripheral dendrons on the photophysical properties and electroluminescent performances of the self‐host materials were systematically investigated. The transient fluorescence and electroluminescence spectra indicated that the diphenylphosphoryl carbazole units could effectively encapsulate the emissive core to reduce the concentration quenching effect and to enhance reverse intersystem crossing. By using tbCz‐SO and poCz‐SO as host‐free blue emitters, the performance of the solution‐processed nondoped OLED device demonstrated that a more balanced charge transfer from the bipolar dendrons would offer a better current efficiency of 10.5 cd A −1 and stable color purity with Commission Internationale de L'Eclairage units of (0.18, 0.27). Abstract : Into the blue : By introducing diphenylphosphine oxide groups, the molecular encapsulation and charge balance properties of a self‐host blue emitter are significantly enhanced. This study not only enriches the types of dendrons that can be used for self‐host blue emitters but also demonstrates the positive effect of bipolar dendrons on the electroluminescent performance of nondoped devices.